Layer-by-layer coating of MIL-100(Fe) on a cotton fabric for purification of water-soluble dyes by the combined effect of adsorption and photocatalytic degradation. Issue 27 (14th June 2022) - Lee, Suhyun; Ahn, Soyeon; Lee, Halim; Kim, Jooyoun
Abstract : A MIL-100(Fe)-based water purifying textile that functions by dual action of adsorption and photocatalytic activity is designed via a layer-by-layer process without using toxic organic solvents. Abstract : Efforts have been made for sustainable development of adsorbents to purify organic contaminants from wastewater. In this study, a MIL-100(Fe) based textile that acts as a reusable adsorbent and photocatalytic agent was developed by synthesizing MIL-100(Fe) onto a cotton fabric by the layer-by-layer (LBL) process using water-based solutions. As the number of LBL cycles increased, the add-on's of MIL-100(Fe) showed a drastic increase up to 8 cycles, then showed gradual increases with further treatments. The overall adsorption performance was enhanced with the increased MIL-100(Fe) add-on's, but the specific adsorption efficiency per unit mass of MIL-100(Fe) was reduced as the LBL cycles increased, implying the reduced average adsorption efficiency with a thicker coating. To examine the reusability of the adsorbent, desorption efficiency of RhB was measured. The desorption after the first-time adsorption was not efficient due to the strong binding inside the pores. For the later cycles of adsorption–desorption, desorption occurred more efficiently, probably because RhB molecules were adhered mostly at the outer surface of the MOF layer. Simultaneously, MIL-100(Fe)@cotton demonstrated the photocatalytic degradation performance against RhB in the presence of H2 O2 by the Fenton reaction. With the combined effect of adsorption and photodegradation, the developed fabric attained 96% removal efficiency for RhB dissolved in water. This study demonstrates an environmentally responsible process of developing a MIL-100(Fe) coated fabric that is readily available for effective removal of organic foulants in water. This fabrication method can be applied as a scalable manufacturing of metal–organic framework-based photocatalytic adsorbent textiles.